Prevalence of sensitisation to cellulase and xylanase in bakery workers. Issue 10 (22nd September 2003) - Elms, J; Fishwick, D; Walker, J; Rawbone, R; Jeffrey, P; Griffin, P; Gibson, M; Curran, A D
Abstract : Aims: To assess the prevalence of sensitisation to a range of exogenous fungal enzymes used in bakeries, and determine the relation between sensitisation and work related symptoms. Methods: Serum samples (n = 135) from a previous cross sectional study investigating the prevalence of respiratory symptoms and sensitisation to dust components, were reanalysed for specific IgE to the mixed enzymes cellulase, hemicellulase, and xylanase. Results: Eight (6%) of sera tested had detectable specific IgE to mixed enzymes (excluding fungal α-amylase) and 16 (12%) to fungal α-amylase. A significant increase (p = 0.03) in nasal symptoms was found in those workers sensitised to enzymes (including α-amylase and the mixed enzymes, but with or without sensitisation to wheat flour) when compared to those sensitised to wheat flour alone. Both groups had significantly greater levels of nasal symptoms in comparison to those with no evidence of sensitisation. Conclusions: The association between specific IgE to mixed enzymes, and an increased prevalence of nasal symptoms in individuals sensitised to enzymes, highlights the importance of measuring sensitisation to the full range of exogenous enzymes used in the baking industry, as well as to wheat flour.